Exploring the Impact of DevOps and Agile Practices from the Perspective of Source Code Analysis - Barros, Jalles Daniel; Oliveira, Luiz Carlos; Oliveira, Johnatan; Padilha, Juliana (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2024: Anais do XII Workshop de Visualização, Evolução e Manutenção de Software, 2024)
Implementing agile practices in software development processes promises improvements in product quality and process productivity. However, there are few reports of failures from which to learn, and it is not always clear which practices are effective in specific contexts. This paper investigates how the use of DevOps and agile methodologies affects code quality in open-source projects hosted on GitHub. A total of 57 Java repositories, obtained through queries to the GitHub GraphQL API, were analyzed and categorized into four groups: i) projects that do not use agile nor DevOps, ii) projects that use agile but not DevOps, iii) projects that use both agile and DevOps, and (iv) projects that use DevOps but not agile. The results indicate that the majority of analyzed projects belong to group iii. Furthermore, the absolute number of code smells and their proportion relative to the number of lines of code are highest in group iii, suggesting a positive correlation between the use of both agile and DevOps practices and an increase in code smells.